The chloroplast genome evolution of Venus slipper (Paphiopedilum): IR expansion, SSC contraction, and highly rearranged SSC regions - Guo, Yan-Yan; Yang, Jia-Xing; Bai, Ming-Zhu; Zhang, Guo-Qiang; Liu, Zhong-Jian (BMC plant biology, 2021)
Background Paphiopedilum is the largest genus of slipper orchids. Previous studies showed that the phylogenetic relationships of this genus are not well resolved, and sparse taxon sampling documented inverted repeat (IR) expansion and small single copy (SSC) contraction of the chloroplast genomes of Paphiopedilum. Results Here, we sequenced, assembled, and annotated 77 plastomes of Paphiopedilum species (size range of 152,130 - 164,092 bp). The phylogeny based on the plastome resolved the relationships of the genus except for the phylogenetic position of two unstable species. We used phylogenetic and comparative genomic approaches to elucidate the plastome evolution of Paphiopedilum. The plastomes of Paphiopedilum have a conserved genome structure and gene content except in the SSC region. The large single copy/inverted repeat (LSC/IR) boundaries are relatively stable, while the boundaries of the inverted repeat and small single copy region (IR/SSC) varied among species. Corresponding to the IR/SSC boundary shifts, the chloroplast genomes of the genus experienced IR expansion and SSC contraction. The IR region incorporated one to six genes of the SSC region. Unexpectedly, great variation in the size, gene order, and gene content of the SSC regions was found, especially in the subg. Parvisepalum. Furthermore, Paphiopedilum provides evidence for the ongoing degradation of the ndh genes in the photoautotrophic plants. The estimated substitution rates of the protein coding genes show accelerated rates of evolution in clpP, psbH, and psbZ. Genes transferred to the IR region due to the boundary shift also have higher substitution rates. Conclusions We found IR expansion and SSC contraction in the chloroplast genomes of Paphiopedilum with dense sampling, and the genus shows variation in the size, gene order, and gene content of the SSC region. This genus provides an ideal system to investigate the dynamics of plastome evolution. Keywords: Orchidaceae, Paphiopedilum, Phylogenomics, Plastome, Boundary shift, IR, SSC boundary, Gene loss, Pseudogenization